2016
DOI: 10.1186/s12862-016-0791-0
|View full text |Cite
|
Sign up to set email alerts
|

How and how much does RAD-seq bias genetic diversity estimates?

Abstract: BackgroundRAD-seq is a powerful tool, increasingly used in population genomics. However, earlier studies have raised red flags regarding possible biases associated with this technique. In particular, polymorphism on restriction sites results in preferential sampling of closely related haplotypes, so that RAD data tends to underestimate genetic diversity.ResultsHere we (1) clarify the theoretical basis of this bias, highlighting the potential confounding effects of population structure and selection, (2) confro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 18 publications
(27 reference statements)
4
66
0
Order By: Relevance
“…Moreover, rare alleles contribute important equilibrium genetic variation (Luikart, Allendorf, Cornuet, & Sherwin, ) and native C. solstitialis populations have been previously shown to harbour more rare alleles than invading populations in North America (Barker et al, ). There is also a tendency for RAD‐seq to underestimate π in more diverse genomes (Arnold, Corbett‐Detig, Hartl, & Bomblies, ; Cariou, Duret, & Charlat, ), although given the loss of rare alleles from invading populations, we might expect this to affect native populations more strongly than invading populations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, rare alleles contribute important equilibrium genetic variation (Luikart, Allendorf, Cornuet, & Sherwin, ) and native C. solstitialis populations have been previously shown to harbour more rare alleles than invading populations in North America (Barker et al, ). There is also a tendency for RAD‐seq to underestimate π in more diverse genomes (Arnold, Corbett‐Detig, Hartl, & Bomblies, ; Cariou, Duret, & Charlat, ), although given the loss of rare alleles from invading populations, we might expect this to affect native populations more strongly than invading populations.…”
Section: Discussionmentioning
confidence: 99%
“…These studies, using both simulated and empirical data, have quantified the number of retained homologous loci among species with varying divergence dates. Simulations suggest that hundreds of orthologous, phylogenetically informative loci can be identified in species with divergence times of up to 60 million years (Cariou, Duret, & Charlat, 2016a,2016b; Rubin, Ree, & Moreau, 2012), but empirical studies have successfully applied RADseq to phylogenetic studies of species only from more recent radiations (<100,000 years; Keller et al., 2013; Wagner et al., 2013) and find that the number of shared SNPs drops, sometimes quickly, as divergence dates increase (Lexer et al., 2013; Pante et al., 2015). Among our two studied seal species, harbor and gray, that diverged approximately 5 mya (Arnason et al., 2006), we found over 100,000 homologous RAD loci.…”
Section: Discussionmentioning
confidence: 99%
“…While both datasets included similar numbers of loci and sequences per individual, many more polymorphic loci and SNPs were identified among gray seal loci than harbor seal loci (Figure 4). We acknowledge that there exist several sources of bias in estimates of genetic diversity from RAD sequencing data (Arnold, Corbett‐Detig, Hartl, & Bomblies, 2013; Cariou, Duret, & Charlat, 2016a,2016b; DaCosta & Sorenson, 2014; Davey et al., 2013; Gautier et al., 2013), but contend that relative comparisons of diversity between species for which data have been collected and processed in a similar manner should be robust (Lozier, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Using simulated data, the authors compared the accuracy and robustness of their F ST estimator under several sources of bias that commonly affect sequencing datasets.They demonstrated that their estimator was robust regarding the variance of coverage across loci and observed that sequencing error implicated a negligible bias for Pool-seq F ST estimates. While simulation studies of Pool-seq and GBS data have already been performed to report sources of bias (e.g.,Arnold, Corbett-Detig, Hartl, & Bomblies, 2013;Cariou, Duret, & Charlat, 2016;Gautier et al, 2013;Guo et al, 2013;Hivert et al, 2018), no study pertaining testing the effect of different levels of pooling, different number of individuals and different number of SNPs on the accuracy of F ST estimates for these three libraries protocols. They also noted that the smaller is the pool size, the higher is the effect of experimental bias.…”
mentioning
confidence: 99%